2021
DOI: 10.47672/ajp.710
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Gender and Coping Strategies among Secondary School Teachers in Kampala District

Abstract: Purpose: The study aimed at assessing the sources of stress among male and female teachers, coping strategies adopted by the teachers and the effects of stress on the job performance of teachers.  Methodology: The study adopted a survey design with both quantitative and qualitative methods.  The study was conducted among secondary school teachers who were picked from both private and government aided schools in Nakawa Division, Kampala District.  The sample consisted of 100 teachers who were selected thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
4
0
0
Order By: Relevance
“…This is in agreement with a previous finding that lecturers who have practiced for 15 years and above have adopted adequate coping strategies over the years to deal with stress [25]. Lecturers who are more advanced in age tend to develop means of coping with the realities of the job in contrast to younger lecturers, and with increased years of practice grow the ability to cope with the presenting workload, job satisfaction, financial remunerations, and family issues [25]. We also speculate that because the promotion of lecturers in Nigeria's educational system draws a greater percentage of points from the literary output, like the publication of research in scientific journals, younger lecturers are also laden with the issue of article publications to earn promotion, hence whittling their coping capacity.…”
Section: Difference In Coping Mechanisms Work-related Stress and Qual...supporting
confidence: 93%
See 3 more Smart Citations
“…This is in agreement with a previous finding that lecturers who have practiced for 15 years and above have adopted adequate coping strategies over the years to deal with stress [25]. Lecturers who are more advanced in age tend to develop means of coping with the realities of the job in contrast to younger lecturers, and with increased years of practice grow the ability to cope with the presenting workload, job satisfaction, financial remunerations, and family issues [25]. We also speculate that because the promotion of lecturers in Nigeria's educational system draws a greater percentage of points from the literary output, like the publication of research in scientific journals, younger lecturers are also laden with the issue of article publications to earn promotion, hence whittling their coping capacity.…”
Section: Difference In Coping Mechanisms Work-related Stress and Qual...supporting
confidence: 93%
“…This study revealed that the sex of lecturers affected their ability to adjust and adapt to their work demands. This finding was supported by the report of a previous study that male lecturers used less social coping than females and there is a significant difference in the coping to stress between male and female lecturers [25]. Also, our finding is in alignment with work done by Graves et al [26] and Kalu et al [27] that agreed on a difference in coping strategies between males and females in the workplace.…”
Section: Difference Between Male and Female Coping Mechanisms Work-re...supporting
confidence: 92%
See 2 more Smart Citations